2021
DOI: 10.3390/biom11040541
|View full text |Cite
|
Sign up to set email alerts
|

Antennal Enriched Odorant Binding Proteins Are Required for Odor Communication in Glossina f. fuscipes

Abstract: Olfaction is orchestrated at different stages and involves various proteins at each step. For example, odorant-binding proteins (OBPs) are soluble proteins found in sensillum lymph that might encounter odorants before reaching the odorant receptors. In tsetse flies, the function of OBPs in olfaction is less understood. Here, we investigated the role of OBPs in Glossina fuscipes fuscipes olfaction, the main vector of sleeping sickness, using multidisciplinary approaches. Our tissue expression study demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 102 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…Together, these data are consistent with a combination of the carrier and presentation models for OBP function and implicate a direct interaction between the LUSH and Or67d–Orco pheromone receptors on the dendrites. Following these studies, many groups have demonstrated specific roles for OBP members in the detection of volatile ligands in many species [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ], and even for tastants and humidity [ 89 , 90 ]. Finally, in Drosophila , an odorant-binding protein has been implicated in blocking sugar taste detection when sucrose is present with bitter compounds [ 91 ].…”
Section: Odorant-binding Proteins (Obps)mentioning
confidence: 99%
“…Together, these data are consistent with a combination of the carrier and presentation models for OBP function and implicate a direct interaction between the LUSH and Or67d–Orco pheromone receptors on the dendrites. Following these studies, many groups have demonstrated specific roles for OBP members in the detection of volatile ligands in many species [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ], and even for tastants and humidity [ 89 , 90 ]. Finally, in Drosophila , an odorant-binding protein has been implicated in blocking sugar taste detection when sucrose is present with bitter compounds [ 91 ].…”
Section: Odorant-binding Proteins (Obps)mentioning
confidence: 99%
“…The number of OBP genes in the genome ranges from 12 to 109 among insect species (Venthur & Zhou, 2018). Functional analyses demonstrated essential roles of several OBPs in olfaction (Xu et al, 2005; Shiota et al, 2018; Diallo et al, 2021), not only in perception, but also in deactivating or moderating odor stimulations (Scheuermann & Smith, 2019; Rihani et al, 2021). The OBP genes are expressed in various organs, such as the brain, reproductive organs, digestive organs, and muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Exactly how invertebrate OBPs affect odorant responses is not clear, but involves direct interactions between binding proteins and odorants. Defects in pheromone and odorant detection have been observed in many insect species lacking specific OBP ( Pophof 2004 ; Laughlin et al 2008 ; Fawaz et al 2014 ; Dong et al 2017 ; Zhang et al 2017 ; Dong et al 2019 ; Scheuermann and Smith 2019 ; Mozuraitis et al 2020 ; Chen et al 2021 ; Diallo et al 2021 ; Du and Chen 2021 ; Gao et al 2021 ; Guo et al 2021 ; Han W-K et al . 2022 ; Tian et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%